LncRNA lnc_13814 promotes the cells apoptosis in granulosa cells of duck by acting as apla-miR-145-4 sponge. Issue 9 (3rd May 2021) - Wu, Yan; Xiao, Hongwei; Pi, Jinsong; Zhang, Hao; Pan, Ailuan; Pu, Yuejin; Liang, Zhenhua; Shen, Jie; Du, Jinping; Huang, Tao
ABSTRACT: Follicle development is a vital factor which determines the reproductive performance of poultry. Long noncoding RNAs (lncRNAs) have been reported to maintain animal reproductive function and play key roles in ovarian development and hormone secretion. But the regulatory mechanism of lncRNAs in duck follicle development has seldom been reported. In this study, to better explore the molecular mechanism of follicle development in ducks, the follicular lncRNA was sequenced and analyzed. A total of 9, 551 lncRNAs were predicted in the duck follicles. Four hundred and forty-five lncRNAs were differentially expressed between the white follicles and yellow follicles. The results of our studies showed that lnc_13814 promoted cell apoptosis in duck GCs. Furthermore, the bioinformatics analysis results demonstrated that lnc_13814 was involved in a lncRNA-miRNA-mRNA coexpression network and it was observed to sponge two follicle-related miRNAs by a luciferase activity assay. Moreover, we found that overexpression of lnc_13814 significantly increased DNA damage inducible transcript 3 (DDIT3) expression and downregulated GCs apoptosis. Finally, we found that lnc_13814 directly binds to and inhibits apla-mir-145-4; then, lnc_13814 increases the expression of DDIT3 and up-regulates GCs apoptosis. Taken together, our findings demonstrate that lncRNAs have potential effects on duck ovarian follicles and lncRNAs may represent a new approach to understand follicular development.